Development of a power model for large wave gear toothing - V. N. Strelnikov; A. I. Voloshin; M. G. Sukov (Advanced Engineering Research, 2019)
Introduction. The development of computational-and-experimental methods for evaluating the force distribution pattern across the width of the toothed rim and in the circumferential direction of the toothing of a large wave gear is considered. The study is based on the results of the test tooth tensometry using scale modeling of prototype units. The work objective is to create a reliable experimental-theoretical model of the teeth force interaction in a large wave gearing. Such a solution involves the transformation of model sample deformations into a distributed load between teeth which will eliminate the basic uncontrollable nonlinear errors and improve the accuracy of estimation of force Materials and Methods. An improved power analysis procedure of a large wave gearing, optimized by accuracy criteria, is developed. The accuracy of the research results is enhanced through improving physical and computational models. This approach enables to obtain reasonable dependences of the power factors distribution in a large wave gearing.Research Results. The design shape of the control tooth is simplified; an invariant profile is introduced over the full width of the ring gear. Thus, non-linear distortions of the experimental results introduced by a variable tooth shape across the width of the ring gear are excluded. In this case, the installation of tensoresistors across the full width of the test tooth is possible. In addition, the proposed solution can establish the dependence of the teeth deformation across the full width of the ring gear, and not only in the extreme areas as suggested by the well-known techniques. The development of perfect physical and mathematical models enables to increase accuracy of the results of theoretical and experimental studies on power processes in the large wave gearing. The scientific-based two-parameter dependences of the force distribution in gearing are obtained.Discussion and Conclusions. Approximation of the involute-tooth profile in the trapezoidal profile has simplified evidence of identity of the elasticity equations and the boundary conditions of mathematical models. The results obtained are applicable in the mathematical simulation of the planar stress state of teeth with nonlinear profiles. Comparative evaluation of errors introduced by deviations of geometry and dimensions of physical models and mathematical analogues supports the experiment correctness and the validity of the quantitative data obtained. The research results can be used in the improved calculation of the design parameters of the gear components in the engineering process of large heavily loaded wave reducers.